Quantifying human resources : uses and analyses - Coron, Clotilde (London : ISTE, Ltd. ; Hoboken : Wiley, 2020)
Since the late 20th Century, Human Resources (HR) has had a legal obligation to produce reports for management in most firms. However, these have long been considered restrictive and are seldom used to improve decision-making. More recently, the emergence of analytics, Big Data and algorithms has enabled a reconfiguration of the uses of quantification in HR. Accompanied by empirical examples, this book presents and defines the different tools and uses of quantification in HR. It studies the effect of these tools on decision-making and ' without subscribing to the myth of objective and rational quantification ' presents the contributions and limits of the use of data in HR, and analyzes the potential risks of excessive quantification. It also discusses the appropriation of these tools by the various players in a company and examines their effects on the position of HR.
4.1.2. Measuring the effects of HR policies -- 4.2. Quantifying in order to legitimize the HR function? -- 4.2.1. Measuring the performance of the HR function -- 4.2.2. Measuring the link between HR function performance and organizational performance -- 4.3. The quantification and risk of HR business automation -- 4.3.1. HR professions with a high risk of automation -- 4.3.2. Support for the employees concerned -- 5. The Ethical Issues of Quantification -- 5.1. Protection of personal data -- 5.1.1. Risks relating to personal data
Print version record.
5.1.2. Obligations and actions of companies with regard to the protection of personal data
John Wiley and Sons
Keywords: Personnel management; Personnel Management; Personnel -- Direction; BUSINESS & ECONOMICS -- Management Science; Personnel management